2019
DOI: 10.1097/dss.0000000000001743
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Laser-Assisted Delivery of Topical Poly-l-Lactic Acid in the Treatment of Upper Lip Rhytides: A Prospective, Rater-Blinded Study

Abstract: BACKGROUND Perioral rhytides are a common complaint among dermatologic patients and can be notoriously stubborn and resistant to therapy. OBJECTIVE We aimed to assess the safety of fractional ablative laser-assisted delivery of topical poly-l-lactic acid (PLLA) suspension in the treatment of upper cutaneous lip rhytides. MATERIALS AND METHODS Prospective, single-arm, rater-blinded trial. Ten subjects with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In total, 48 published studies of AF LADD met inclusion criteria (eFigure in the Supplement): 4 cosmetic studies,, 21 oncologic, and 23 medical (not cosmetic/oncologic) . In addition, 6 publications of NAF LADD were included at the request of the expert panel, for a total of 54 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 48 published studies of AF LADD met inclusion criteria (eFigure in the Supplement): 4 cosmetic studies,, 21 oncologic, and 23 medical (not cosmetic/oncologic) . In addition, 6 publications of NAF LADD were included at the request of the expert panel, for a total of 54 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Abbreviation: GRADE, Grading of Recommendations Assessment, Development and Evaluation. a These are provided for illustrative purposes and are based on published reports b Level of evidence and strength of recommendation were determined by the guideline panel for the specific indication, but not necessarily for a particular technique or topical agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, there was not any available data about the pro-penetration of HA. We could found two publications [22,23] about the LAD of poly-L-lactic acid to treat atrophic scars and upper lip wrinkles. To treat these conditions, a high density and thus an increased impact of the CO2 laser was needed to have a clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…PLLA is a synthetic substance that not only acts as a filler for subcutaneous injection but also promotes collagen production and vascularization; histological findings have shown that skin thickness increases after treatment. 13,14 PLLA is usually limited in its absorption into the skin owing to its large particle size. To overcome this, we set the spot size of fractional CO2 to 120 μm and used a tightly controlled size of 30-50-μm PLLA to complement the existing large particle size.…”
Section: Discussionmentioning
confidence: 99%